The Existence of the Sharia Supervisory Board in Sharia Savings and Loan and Financing Cooperatives in Pidie Regency - M. Hafizh Achsan; M. Jafar; Teuku Ahmad Yani (International Journal of Law, Crime and Justice, 2026)
Sharia Savings and Loan and Financing Cooperatives (KSPPS) are financial institutions that operate based on Islamic principles and are legally required to establish a Sharia Supervisory Board (SSB) under Qanun Aceh Number 11 of 2018, Law Number 6 of 2023 on Job Creation, and the Regulation of the Minister of Cooperatives and Small and Medium Enterprises Number 8 of 2023. However, several cooperatives in Pidie Regency continue to conduct sharia-based business without amending their Articles of Association or establishing an SSB. This study examines the legal position of the SSB, the obstacles preventing amendments to cooperative Articles of Association, and government efforts to encourage compliance. Using an empirical juridical method with a socio-legal approach, data were collected through interviews, observations, and document analysis and analyzed descriptively. The findings show that the SSB plays a strategic role in ensuring sharia compliance, yet its implementation in Pidie Regency remains limited. Key obstacles include inadequate legal understanding among cooperative management, limited human resources, complex amendment procedures, and insufficient government guidance. Strengthened institutional supervision through capacity building, technical assistance, facilitation of SSB establishment, regular monitoring and evaluation, and consistent enforcement of administrative sanctions is necessary to improve compliance with legal and sharia requirements.